THE EFFECT OF DIFFERENCES IN STOCKING DENSITY ON THE GROWTH AND SURVIVAL OF SNAKEHEAD FISH (Channa striata) JUVENILE IN THE BUCKET FISH CULTIVATION METHOD (BUDIKDAMBER). - Fadillah, Abil; Grandiosa, Roffi; Iskandar, Iskandar; Zidni, Irfan (Universitas Mataram, 2025)
The problem in cultivating snakehead fish in budikdamber media is the most effective stocking density and how the budikdamber system affects the growth and survival of snakehead fish seeds, this study aims to determine the effective stocking density of snakehead fish in the budikdamber method. The method used in this study is the experimental method of Completely Randomized Design (CRD), which consists of three treatments and five replications. The treatments used are (A) stocking density of 50 fish/70 liter (control), (B) stocking density of 60 fish/70 liter, and (C) stocking density of 70 fish/70 liter, which are maintained for 40 days. The test fish used are snakehead fish with a length of 6-8 cm and a weight of 3-4 g. The container used is a plastic bucket with a volume of 80 liters with the water volume of 70 liters where the snakehead fish are placed with a stocking density according to the treatment. The amount of feed given is 5% of the fish biomass. The results obtained during the study showed that treatment C with a density of 70 fish/70 liters produced the highest absolute length growth of 2,56±0,5 cm, the highest absolute weight growth of 4,55±0,99 gram, the highest specific growth rate of 2,08±0,09 %, and survival of 94±0,05%